2023
DOI: 10.1101/2023.08.30.555491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual antagonism and sex determination in three syngnathid species alongside a male pregnancy gradient

Arseny Dubin,
Jamie Parker,
Astrid Böhne
et al.

Abstract: Teleost fish show an enormous diversity of sex determination systems, varying from environmental sex determination to full sex chromosomes. Traditionally sex chromosomes are considered within a framework of sexually antagonistic relationships and are viewed not only as sex determination systems but also as a means to resolve sexual conflict by confining conflicting genes to one sex. However, the relationship between emergence sexually-antagonistic loci, resolution of sexual conflict and sex determination is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 229 publications
0
5
0
Order By: Relevance
“…We found that the gonads especially, but livers as well, displayed sex-biased patterns of expression, and the genes that were sex-biased in one organ were generally not sex-biased in the others. In the gills, which do not serve a reproductive function, we observed only a small number of differentially expressed genes, but those that were differentially expressed generally were related to immunity, similar to other pipefishes (Dubin et al, 2023;Pappert et al, 2023). Genes that had the largest bias in expression while still being expressed in both sexes also tended to be tissue specific in their expression patterns, suggesting that sex-biased expression might more readily evolve in genes with fewer pleiotropic constraints.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…We found that the gonads especially, but livers as well, displayed sex-biased patterns of expression, and the genes that were sex-biased in one organ were generally not sex-biased in the others. In the gills, which do not serve a reproductive function, we observed only a small number of differentially expressed genes, but those that were differentially expressed generally were related to immunity, similar to other pipefishes (Dubin et al, 2023;Pappert et al, 2023). Genes that had the largest bias in expression while still being expressed in both sexes also tended to be tissue specific in their expression patterns, suggesting that sex-biased expression might more readily evolve in genes with fewer pleiotropic constraints.…”
Section: Discussionmentioning
confidence: 52%
“…Several sex-specific genes reinforce this pattern of sex differences in immune function in the gill, such as vascular cell adhesion protein 1 and galactose-specific lectin nattectin, which are male-specific in both gonads and gills and have been shown in zebrafish and multiple finfish to be related to immune responses (Elumalai et al, 2019;Hsieh et al, 2018). Differences in immune function between males and females have previously been demonstrated in pipefish (Dubin et al, 2023;Pappert et al, 2023;Roth et al, 2011), and the male-specific patterns of expression we observed could support the hypothesis the pregnant male pipefish experience different selection pressures with regard to immunity compared to female and non-pregnant pipefish (J. Parker et al, 2023;Roth et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations